If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + -62 = 7x + 10 + 11x Reorder the terms: -62 + 12x = 7x + 10 + 11x Reorder the terms: -62 + 12x = 10 + 7x + 11x Combine like terms: 7x + 11x = 18x -62 + 12x = 10 + 18x Solving -62 + 12x = 10 + 18x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-18x' to each side of the equation. -62 + 12x + -18x = 10 + 18x + -18x Combine like terms: 12x + -18x = -6x -62 + -6x = 10 + 18x + -18x Combine like terms: 18x + -18x = 0 -62 + -6x = 10 + 0 -62 + -6x = 10 Add '62' to each side of the equation. -62 + 62 + -6x = 10 + 62 Combine like terms: -62 + 62 = 0 0 + -6x = 10 + 62 -6x = 10 + 62 Combine like terms: 10 + 62 = 72 -6x = 72 Divide each side by '-6'. x = -12 Simplifying x = -12
| x+(x+5)=6 | | (8^-3y^4/x^2y^6)^2 | | 6x-62=-5x+4 | | -y+16y=-15 | | 0=10x^2+21x-10 | | 7+5lnx=6 | | 0=21x^2+40x-21 | | 5a(5a+x)=2a(2a-x) | | -(-3y)-y=-10 | | 1596.5=9/5C+32 | | m=1/5(7) | | 20x^3-3=11x | | ((x^-2*y^3/x^4*y^10))^2 | | k^2-17x+72=0 | | C(x)=62+34x-x^2 | | 10+6n=5-n | | 20b^2-15b=5b | | -7=-2x-1 | | (x^-2*y^3/x^4*y^10) | | -1y=7 | | 4x^3+32x^2+60x=0 | | (7/x+6)+3/x | | 7/x+6+3/x | | -4-(3-6p)= | | -4(3-6p)= | | -45+6x=-57 | | 50q=-q^2+8400 | | (5x+7)(x^2+x-2)=0 | | 263+y=360 | | 3n-36=27 | | 108n=(n-2)180 | | -3(4s-3)-9=-2(9s+5)-3 |